PENGARUH JUMLAH PEG 200 DAN TEMPERATUR ANNEALING TERHADAP MORFOLOGI DAN STRUKTUR NANOPARTIKEL TiO2 DENGAN METODE SINTESIS SIMPLE HEATING - Tuty Emilia Agustina; Fitri Suryani Arsyad; Mikrajuddin Abdullah (Environmental Research Center (PPLH) of Udayana University, 2013)
The surface area of a photocatalyst is an important factor that effect decomposition process of colored wastewater. Increasing the catalyst particle surface area will increase the UV light absorbed thus enhance the photacatalysis process. Bulk TiO2 will have the higher surface area if it is made in the nano size. As a photocatalyst, nanoparticle of TiO2 is more efficient than bulk of TiO2. The nanoparticle of TiO2 can be made in various ways, for example by simple heating method. In this study, the synthesis of nanoparticle TiO2 was investigated by optimize the amount of polyethilene glycol (PEG 200) used and the annealing temperature. The amount of PEG 200 was varied between 6-18 ml. Moreover, the annealing temperature was varied in the range of 600-700oC. After synthesizing, the nanoparticles of TiO2 then characterize by using scanning electron microscope (SEM) to observe the morphology, and by using the X-ray difraction (XRD) to find the crystal structure and the particle size. Based on the characterization, it was found that the smallest nanoparticle of TiO2 have a 29 nm in size was produced by using the 12 ml of PEG at the annealing temperature of 600oC.